História, Histórias e Paradoxografia: Opera Omnia - Reina Marisol Troca Pereira (Classica Digitalia: Autores Gregos e Latinos: textos, 2019)
Late classical author of Greek expression, Phlegon of Tralles was recognized for centuries, through his work. Most of the books of the emperor Hadrian's freedman are currently lost, with the exception of some fragments and sections of On Marvels, On Long-Lived Persons and the Olympiads. It could be just another legacy to add to so many others. However, the writing of Flégon is enriching, preserving oriental notes; the cultural assimilation undertaken by the Roman military dominators; the experience and the value of pagan traditional elements in a Judeo-Christian paradigm which in some cases demonstrates the misappropriation and misuse of some statements made by the Historian from Tralles. The themes can simply be understood as light issues of popular taste, marked by the exploration of grotesque and astonishing themes. However, a distinct exegesis will provide the elevation of Phlegon's opuscula, as enigmatic containers of social realities maintaining an up-to-date character.